Management Evaluation of Metastasis in the Brain (MEMBRAIN) – A UK & Ireland prospective, multicentre observational study. (12th October 2019) - Jung, Josephine; Tailor, Jignesh; Dalton, Emma; J Glancz, Laurence; Roach, Joy; Zakaria, Rasheed; P Lammy, Simon; Chari, Aswin; P Budohoski, Karol; J Livermore, Laurent; Yu, Kenny; D Jenkinson, Michael; et al.
Abstract: Background: Over the recent years an increasing number of patients with brain metastasis are being referred to the neuro-oncology multi-disciplinary team (NMDT). Our aim was to determine if referrals of this group of patients to the NMDT in the UK & Ireland comply with NICE guidelines and to assess referral volume, quality of information provided and its impact on NMDT decision-making. Methods: Prospective multicentre oberservational study including all adult patients referred with ≥1 cerebral metastasis. Data was collected in neurosurgical units from 11/2017 to 02/2018. Demographics, primary disease, Karnofsky performance status (KPS), imaging and treatment recommendation were entered into an online database. Results: 1049 patients were analysed from 24 neurosurgical units. Median age was 63[range 21–93] years with a median number of 3[range 1–17] referrals per NMDT. The most common primary malignancies were lung (36.5%, n=383), breast (18.5%, n=194) and melanoma (12.0%, n=126). 51.6% (n=541) of the referrals to the NMDT were within the NICE 2006 guidelines, and resulted in specialist intervention being offered in 68.8%. 41.2% (n=197) of patients being referred outside of the NICE 2006 guidelines were offered specialist treatment. NMDT decision-making was influenced by number of metastases, age, KPS, primary disease status and extent of extracranial disease (univariate logistic regression, p<0.0001) as well as metastasis location/histology (p<0.05). Conclusions: This study confirmed a national change in culture of referral patterns. We identified a delay in NMDT decision-making in ~20%, contributing to increased NMDT workload. New stratification tools may be needed to reflect advancements in diagnostics and treatment modalities.